N7-methylguanosine (m7G) tRNA modification: a novel autophagy modulator in cancer. Issue 1 (2nd January 2023) - Han, Hui; Zheng, Siyi; Lin, Shuibin
ABSTRACT: Macroautophagy/autophagy, a physiological process that is involved in tumorigenesis, is regulated at genetic and epigenetic levels. Emerging reports suggest that aberrant RNA modifications cause dysregulated autophagy and affect tumorigenesis, while the role of RNA modifications in the regulation of autophagy in cancers remains unclear. In a recent study, we describe a new role for the tRNA m 7 G methyltransferase complex components METTL1 and WDR4 as negative regulators of MTORC1-mediated autophagy in esophageal squamous cell carcinoma (ESCC). METTL1 and WDR4 show abnormally high expression in ESCC tissues, and are associated with poor ESCC prognosis. Targeting METTL1 or WDR4 leads to decreased expression of m 7 G-modified tRNAs and reduces the translation of a subset of oncogenic transcripts, including the genes related to the MTOR signaling pathway and negative regulators of autophagy in an m 7 G-related codon-dependent manner, thereby resulting in hyperactivated MTORC1-mediated autophagy via dephosphorylation of ULK1 and finally causes cell death in ESCC. Our findings provide a new layer of translation regulation mechanism mediated by tRNA m 7 G modification, link translational machinery with autophagic machinery, and suggest that METTL1 and its downstream signaling axis could be potential therapeutic targets for ESCC treatment.